Help!!!!!!!!!!!!!!!!!!!!!!!!!!!
Help!!!!!!!!!!!!!!!!!!!!!!!!!!! - 1

Answers

Answer 1
Answer: 3 quarts because you need to convert the 1 cup into quarts because it says how many QUARTS not CUPS. 1 cup = 0.25 quarts. 0.25 x 12 cakes = 3!

at least i think its correct... sorry and good luck!
Answer 2
Answer: ITS SO OBVIOUS IM SORRY! You have to times 1x12=12.
1 QUART PER CAKE. HOW MANY FOR 12?  12.

ANSWER IS 12! its so obvious lol (im not mad or nun) XD :D


Related Questions

Which associations best describe the data in the table?Variable j 2 4 6 3 7 9 1 5 8Variable k 48 43 33 46 20 6 52 40 18Choose exactly two answers that are correct.A.linear associationB.negative associationC.nonlinear associationD.positive association
Since I have alot of points I'mma give it away to yall....IF you answer my multiple questions,,I'll give you 50+ Points
In a group of 48 children there are three times as many boys as girls. how many girls are there
Try to simplify 72/6+85/6
In a video game, a guppy that escapes a net turns into three goldfish. Each goldfish can turn into two betta fish. Each betta fish can turn into two angelfish. Complete the diagram and write the number of fish at each stage. Write and evaluate an expression for the number of angelfish that can be formed from one guppy

Answers

AAAA
BBAB
ABAB
ABBB
BABA
(I can choose multiple)

Answers

Answer:

BBAB, ABAB, and BABA

Step-by-step explanation:

Use the probability/combination theorem.

R^2 + 4r = 0 please show work

Answers

{ r }^( 2 )+4r=0\n \n r\left( r+4 \right) =0\n \n \therefore \quad r=0\quad \wedge \quad r=-4
r^2 + 4r = 0\nr(r+4)=0\nr=0 \vee r=-4

the first term in a sequence is an odd number the rule is to multiply by 2 explain why the rest of the terms in the sequence will be even numbers.

Answers

If you do that, then 2 will be a factor of all the terms after the first one.  
And any number that has 2 as a factor is an even number.

4h - 6= 22-8s + 1= 33
-4w - 4= 8
5 +1/7b = -2
i need help on these problems!

Answers

4h−6=22
1. Add 6 to both sides.
4h−6+6=22+6
4h=28
2.Divide both sides by 4.
4h/4=28/4
h=7

−8s+1=33
1: Subtract 1 from both sides.
−8s+1−1=33−1
−8s=32
2: Divide both sides by -8.
−8s/−8=32/−8
s=-4


4w
−4
=8
Step 1: Add 4 to both sides.
4w−4+4=8+4
4w=12
2: Divide both sides by -4.
4w/−4=12/−4
w=−3


Step 1: Simplify both sides of the equation.

1/7b+5=−2
 2: Subtract 5 from both sides.
1/7b+5−5=−2−5
17b=−7
3: Multiply both sides by 7.
7*(1/7b)=(7)*(−7)
b=−49

Please answer and put how

Answers

6 + m/4 = 3 (subtract 6 from both sides)
m/4 = -3 (multiply both sides by 4)
m = -12

Can plug in to original equation to check work:
6 - 12/4 = 3
6 - 3 = 3
3 = 3 

The answer m = -12 checks out
 first you write out the equation 
subtract 6 from both sides
then multiply both sides by 4
because if you multiply something to one side you have to do it to the other one too
m = -12
 you can then check work like this
6 - 12/4 = 3
6 - 3 = 3
3 = 3 

 (m = -12 subtract 6 from both sides)
(m/4 = -3 then you multiply both sides by 4)

Using the property find the sum: (4/3 + 3/5 + "-2/3" + "-11/5)"

Answers

Answer:

-14/15

Step-by-step explanation:

First the denominator must be the same so mutiply three with 5 to get 15. Don't forget to mutiply numrator!

After that, sump up the first numerator and second numerator because both are plus so you will get 29

Then, sum up the third numrator and forth numrator because both are minus so you will get -43.

Finally, you have 29 + -43 by 15.

You have to substract small number from large number so you will get -14. We use minus sign because -43 is larger than 29.

The result of (4/3+3/5+-2/3+-11/5) -87/15 or -5.8